Differential protease activity augments polyphagy in helicoverpa armigera - Chikate, Yojana R.; Tamhane, V. A.; Joshi, Rakesh S.; Gupta, Vidya S.; Giri, Ashok P. (Insect Molecular Biology, 2013)
Helicoverpa armigera (Lepidoptera: Noctuidae) and other polyphagous agricultural pests are extending their plant host range and emerging as serious agents in restraining crop productivity. Dynamic regulation, coupled with a diversity of digestive and detoxifying enzymes, play a crucial role in the adaptation of polyphagous insects. To investigate the functional intricacy of serine proteases in the development and polyphagy of H.armigera, we profiled the expression of eight trypsin-like and four chymotrypsin-like phylogenetically diverse mRNAs from different life stages of H.armigera reared on nutritionally distinct host plants. These analyses revealed diet- and stage-specific protease expression patterns. The trypsins expressed showed structural variations, which might result in differential substrate specificity and interaction with inhibitors. Protease profiles in the presence of inhibitors and their mass spectrometric analyses revealed insight into their differential activity. These findings emphasize the differential expression of serine proteases and their consequences for digestive physiology in promoting polyphagy in H.armigera.
Keywords: adaptation; chymotrypsin; Helicoverpa armigera; polyphagy; Trypsin

Differential antibiosis against helicoverpa armigera exerted by distinct inhibitory repeat domains of capsicum annuum proteinase inhibitors - Joshi, Rakesh S.; Gupta, Vidya S.; Giri, Ashok P. (Phytochemistry, 2014)
Plant defensive serine proteinase inhibitors (Pis) are known to have negative impact on digestive physiology of herbivore insects and thus have a crucial role in plant protection. Here, we have assessed the efficacy and specificity of three previously characterized inhibitory repeat domain (IRD) variants from Capsicum annuum PIs viz., IRD-7, -9 and -12 against gut proteinases from Helicoverpa armigera. Comparative study of in silico binding energy revealed that IRD-9 possesses higher affinity towards H. armigera serine proteinases as compared to IRD-7 and -12. H. armigera fed on artificial diet containing 5 TIU/g of recombinant IRD proteins exhibited differential effects on larval growth, survival rate and other nutritional parameters. Major digestive gut trypsin and chymotrypsin genes were down regulated in the IRD fed larvae, while few of them were up-regulated, this indicate alterations in insect digestive physiology. The results corroborated with proteinase activity assays and zymography. These findings suggest that the sequence variations among Pis reflect in their efficacy against proteinases in vitro and in vivo, which also could be used for developing tailor-made multi-domain inhibitor gene(s). (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Capsicum annuum; Helicoverpa armigera; Inhibitory repeat domain; Proteases; Proteinase inhibitors

Discovery of potential multi-target-directed ligands by targeting host-specific SARS-CoV-2 structurally conserved main protease - Joshi, Rakesh S.; Jagdale, Shounak S.; Bansode, Sneha B.; Shankar, S. Shiva; Tellis, Meenakshi B.; Pandya, Vaibhav Kumar; Chugh, Anita; Giri, Ashok P.; Kulkarni, Mahesh J. (Journal of Biomolecular Structure & Dynamics, 2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has resulted in the current COVID-19 pandemic. Worldwide this disease has infected over 2.5 million individuals with a mortality rate ranging from 5 to 10%. There are several efforts going on in the drug discovery to control the SARS-CoV-2 viral infection. The main protease (M-Pro) plays a critical role in viral replication and maturation, thus can serve as the primary drug target. To understand the structural evolution of M-Pro, we have performed phylogenetic and Sequence Similarity Network analysis, that depicted divergence of Coronaviridae M-Pro in five clusters specific to viral hosts. This clustering was corroborated with the comparison of M-Pro structures. Furthermore, it has been observed that backbone and binding site conformations are conserved despite variation in some of the residues. These attributes can be exploited to repurpose available viral protease inhibitors against SARS-CoV-2 M-Pro. In agreement with this, we performed screening of similar to 7100 molecules including active ingredients present in the Ayurvedic anti-tussive medicines, anti-viral phytochemicals and synthetic anti-virals against SARS-CoV-2 M-Pro as the primary target. We identified several natural molecules like delta-viniferin, myricitrin, taiwanhomoflavone A, lactucopicrin 15-oxalate, nympholide A, afzelin, biorobin, hesperidin and phyllaemblicin B that strongly binds to SARS-CoV-2 M-Pro. Intrestingly, these molecules also showed strong binding with other potential targets of SARS-CoV-2 infection like viral receptor human angiotensin-converting enzyme 2 (hACE-2) and RNA dependent RNA polymerase (RdRp). We anticipate that our approach for identification of multi-target-directed ligand will provide new avenues for drug discovery against SARS-CoV-2 infection. Communicated by Ramaswamy H. Sarma
Keywords: Coronavirus; COVID-19; hACE-2; MPro; multi-target-directed ligand; protease inhibitor; RdRp; SARS-CoV-2 virus

Developing a feeding assay system for evaluating the insecticidal effect of phytochemicals on Helicoverpa armigera - Mohite, Sharada D.; Patil, Yogita P.; Nichit, Vikram J.; Joshi, Rakesh S. (Jove-Journal of Visualized Experiments, 2023)
Helicoverpa armigera, a lepidopteran insect, is a polyphagous pest with a worldwide distribution. This herbivorous insect is a threat to plants and agricultural productivity. In response, plants produce several phytochemicals that negatively impact the insect's growth and survival. This protocol demonstrates an obligate feeding assay method to evaluate the effect of a phytochemical (quercetin) on insect growth, development, and survival. Under controlled conditions, the neonates were maintained until the second instar on a pre-defined artificial diet. These second-instar larvae were allowed to feed on a control and quercetin-containing artificial diet for 10 days. The insects' body weight, developmental stage, frass weight, and mortality were recorded on alternate days. The change in body weight, the difference in feeding pattern, and developmental phenotypes were evaluated throughout the assay time. The described obligatory feeding assay simulates a natural mode of ingestion and can be scaled up to a large number of insects. It permits one to analyze phytochemicals' effect on the growth dynamics, developmental transition, and overall fitness of H. armigera. Furthermore, this setup can also be utilized to evaluate alterations in nutritional parameters and digestive physiology processes. This article provides a detailed methodology for feeding assay systems, which may have applications in toxicological studies, insecticidal molecule screening, and understanding chemical effects in plant-insect interactions.

Domain shuffling and site-saturation mutagenesis for the enhanced inhibitory potential of amaranthaceae α-amylase inhibitors - Rane, Ashwini S.; Nair, Vineetkumar S.; Joshi, Rakesh S.; Giri, Ashok P. (Protein Journal, 2023)
Amaranthaceae a-amylase inhibitors (AAIs) are knottin-type proteins with selective inhibitory potential against coleopteran a-amylases. Their small size and remarkable stability make them exciting molecules for protein engineering to achieve superior selectivity and efficacy. In this report, we have designed a set of AAI pro- and mature peptides chimeras. Based on in silico analysis, stable AAI chimeras having a stronger affinity with target amylases were selected for characterization. In vitro studies validated that chimera of the propeptide from Chenopodium quinoa a-AI and mature peptide from Beta vulgaris a-AI possess 3, 7.6, and 4.26 fold higher inhibition potential than parental counterparts. Importantly, recombinant AAI chimera retained specificity towards target coleopteran a-amylases. In addition, to improve the inhibitory potential of AAI, we performed in silico site-saturation mutagenesis. Computational analysis followed by experimental data showed that substituting Asparagine at the 6th position with Methionine had a remarkable increase in the specific inhibition potential of Amaranthus hypochondriacus a-AI. These results provide structural-functional insights into the vitality of AAI propeptide and a potential hotspot for mutagenesis to enhance the AAI activity. Our investigation will be a toolkit for AAI's optimization and functional differentiation for future biotechnological applications.
Keywords: & alpha; -Amylase; -Amylase inhibitors; Amaranthaceae; Coleoptera; Peptide; Pest control